PERTANGGUNGJAWABAN PIDANA PELAKU PENGGELAPAN DALAM JABATAN DI PT. TUNAS BARU LAMPUNG (STUDI PUTUSAN NOMOR 96/PID.B/2022/PN.GNS) - Zulfi Diane Zaini; Yulia Hesti; Bayu Chandra Wijaya (YUSTISI, 2023)
Among several criminal acts related to assets and objects, there is a crime known as embezzlement where abuse of trust dominates as the main element in the occurrence of this crime. The problem in this study is what are the factors that cause the perpetrator to commit the crime of embezzlement in his position at PT. Tunas Baru Lampung based on Decision Number 96/Pid.B/2022/PN.Gns, What is the criminal responsibility for the perpetrators of embezzlement in positions at PT. Tunas Baru Lampung based on Decision Number 96/Pid.B/2022/PN.Gns. The factor that caused the defendant to commit embezzlement was due to economic factors where the defendant wanted to control the goods and then sell them and the money from the sale would be divided into three and the defendant would use the money for daily needs. The defendant is responsible for his actions based on Article 374 of the Criminal Code. In conjunction with Article 55 paragraph (1) 1st of the Criminal Code, the defendant was sentenced to nine months in prison. Keywords: criminal liability, embezzlement, in office